The Influence of Islamic Religious Education on Student Behavior at State Junior High School 2 Purwodadi - Chumaedi, Ahmad (Strata Social and Humanities Studies, 2024)
The Influence of Islamic Religious Education Subject on Student Behavior (A Case Study at SMP Negeri 2 Purwodadi). This research is motivated by a problem or phenomenon of middle school students who misbehave as students, like some students smoke, behave rudely, use vulgar language, skip school, are too lazy to study, and so on. The problem addressed in this study is the impact of Islamic religious education on students' behavior, namely in promoting good manners and politeness as expected. The objective is to determine how much Islamic religious education influences student behavior. This study is a quantitative research with a correlational design. The research subjects consist of 105 students from SMP Negeri 2 Purwodadi from the 8th and 9th grades in the academic year 2022/2023. These students were selected from a population of 1425 students. Research analysis has shown that a well-designed PAI learning variable has a significant impact on student behavior.